1989
DOI: 10.1007/bf00510082
|View full text |Cite
|
Sign up to set email alerts
|

Light-induced skin lesions in lupus erythematosus: photobiological studies

Abstract: To investigate the light sensitivity to various wavelength regions in lupus erythematosus (LE), phototests were performed in 24 LE patients with clinical photosensitivity (7 had systemic LE, 9 discoid LE, and 8 subacute cutaneous LE). Skin areas (measuring 40-60 cm2) were irradiated daily, maximally six times. With all three light sources used (emitting UVB, UVA, and visible light respectively) abnormal papular or papulosquamous reactions could be induced. In four of the 20 patients reacting abnormally, lesion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
34
0

Year Published

1992
1992
2013
2013

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 10 publications
2
34
0
Order By: Relevance
“…In recent years, our group has demonstrated that pathologic skin reactions can be induced in 54% of patients with various subtypes of LE, when applying standardized protocols of provocative phototesting (12). Interestingly, as confirmed by other investigators (13)(14)(15), the development of UV light-induced skin lesions is considerably slower and the persistence is longer than in other photodermatoses, such as polymorphous light eruption (PLE).…”
mentioning
confidence: 55%
“…In recent years, our group has demonstrated that pathologic skin reactions can be induced in 54% of patients with various subtypes of LE, when applying standardized protocols of provocative phototesting (12). Interestingly, as confirmed by other investigators (13)(14)(15), the development of UV light-induced skin lesions is considerably slower and the persistence is longer than in other photodermatoses, such as polymorphous light eruption (PLE).…”
mentioning
confidence: 55%
“…10 For a long period of time, the action spectrum was ascribed to the UVB range despite experimental evidence from in vitro and animal studies indicating that UVA irradiation also had specific detrimental effects in CLE. 11,12 In 1986, Lehmann et al 13 were the first to demonstrate experimental induction of skin lesions by UVB and UVA irradiation using a standardized test protocol. A total of 128 patients with different subtypes of CLE underwent phototesting with polychromatic UVB and longwave UVA irradiation 14,15 ; 43% of the tested patients developed characteristic skin lesions that clinically and histologically resembled CLE.…”
mentioning
confidence: 99%
“…The previous results of photoprovocation studies in CLE patients were variable and ranged from 24 -83% positivity (17,31,32). These discrepancies may largely be explained by the variability of photoprovocation protocols and the differences in the types of CLE patients.…”
Section: Discussionmentioning
confidence: 82%